If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -6 = 3x + -2 Reorder the terms: -6 + -1x = 3x + -2 Reorder the terms: -6 + -1x = -2 + 3x Solving -6 + -1x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + -1x + -3x = -2 + 3x + -3x Combine like terms: -1x + -3x = -4x -6 + -4x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -4x = -2 + 0 -6 + -4x = -2 Add '6' to each side of the equation. -6 + 6 + -4x = -2 + 6 Combine like terms: -6 + 6 = 0 0 + -4x = -2 + 6 -4x = -2 + 6 Combine like terms: -2 + 6 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| x=3x^2-x-4 | | 16x-6=10x | | 8+6(x+5)=4x-(3x+9) | | 9y(5)-2(2+7-18)= | | x=x^2-10x-11 | | 5y=12x-8 | | 20x+14y=3748 | | X(1-x)=0.02 | | 3x-9=3x+9 | | .5a^2+a-12=0 | | -4x-7(1-x)=-11x+9(3x+5) | | (x-3.5)^2/3=150 | | 32=5+-3t | | -1/2x+3=x-7 | | x=x+(.005n*x) | | (4x^2-3x^3)-(9x^2-5x^3)=-5x^2+2x^3 | | -4x-7(1-x)=11x+9(3x+5) | | -6x^2+64x+192=0 | | 4x^2+8x-26=(x+3)(x-2) | | 20x+10=80x+50 | | y=x+(.06*x) | | 6x+3=4x-13 | | z^2+6z-9=6z | | 3(x+6)=7x-14 | | -3x^2+32x+96=0 | | 2(0)-5x=10 | | (4x^2-3x^3)-(9x^2-5x^3)=-3x^5 | | y=x+(.005n*x) | | 4x-8=33 | | X(4x)=64 | | 1/3y=x | | 11+12k=-25 |